The pedagogical relevance of certainties from the teacher's perspective - Ariso Salgado, José María (Revista Española de Pedagogía, 2017)
Taking into account that the pedagogical implications of Ludwig Wittgenstein's On, Certainty have scarcely been addressed in the existing literature, this paper presents the basic concepts of the mentioned work, especially the concept of 'certainty', by illustrating how they are implicit in any classroom practice or activity. On this basis, it is subsequently explained, among other things, the role of certainties within pupil's prior knowledge, the way of tackling pupil's doubts about certainties, the facilitation of the adoption of certainties by using negative knowledge, and the way of assessing such adoption. This is intended to show that the work of the teacher is largely enriched if he becomes aware of the pedagogical relevance of certainties.
Keywords: socialization process; certainty; knowledge; world-picture; Ludwig Wittgenstein; JCR